Reimagining Community Engagement Sustainability: Insights for the Postpandemic World - Deanna M. Kennedy; Kara Adams; Dan Bustillos; Shauna Carlisle; Mabel C. Ezeonwu; Deborah A. Hathaway; Grace Lasker; Avery Shinneman (The University of Alabama, 2022)
Scholars in the community engagement field have long discussed measures to sustain community engagement on campus. When COVID-19 emerged, however, university operations, including community-engaged teaching and research, had to pivot. The conversation was no longer about sustaining community engagement but about enduring the pandemic for the sake of students, faculty, and community. In order to inform a more durable community engagement strategy for the postpandemic world, we apply a sensemaking approach for the purpose of organizational learning. We collected quantitative data about 40 planned courses and surveyed 22 community-engaged faculty from April to August 2020 (spring-summer academic quarters). In the same period, we gathered qualitative data from 41 respondents comprising 28 faculty and 13 community partners. The quantitative analysis suggested that, overall, faculty maintained a positive outlook regarding the strategies they used to address the needs of students and community partners and regarding their own expectations and innovations. The qualitative data revealed seven themes-loss and challenge, future uncertainty, action strategies, communication strategies, technology, collaborative resilience, and student considerations-that can help us consider community engagement through the lenses of experience, adaptation, and sustainability. The insights provided here offer ways to improve durability within sustainable community engagement practices.